The Love Surgeon : A Story of Trust, Harm, and the Limits of Medical Regulation - Rodriguez, Sarah B. (Book collections on Project MUSE., 2020)
"Dr. James Burt thought women were made wrong, but that he could make them right. Practicing in Ohio, Burt gradually altered episiotomy repair from the 1950s through the 1970s in order to, he claimed, enhance women's sexual responses. In 1989, in response to malpractice lawsuits, misconduct charges, and negative media coverage, Burt gave up his medical license. The media covering Burt in the late 1980s framed the story as a failure of obtaining informed consent and Burt as an outlier who should have been stopped by his peers. The Burt story raises these questions, and all concern professional self-regulation. They have not been satisfactorily answered, though they were, and remain, central to patient safety. By engaging with the complexity of what happened, A Not so Secret Surgery tells for the first time the absorbing - and at times unsettling - history of James Burt, his surgery, and his patients within the realities of professional self-regulation"--